2013
DOI: 10.1111/vox.12016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of human neutrophil antigen‐1, ‐3, ‐4 and ‐5 allele frequencies in English Caucasoid blood donors using a multiplex fluorescent DNA‐based assay

Abstract: A multiplex Luminex bead assay for the simultaneous detection of HNA-1, HNA-3, HNA-4 and HNA-5 alleles is described that enables rapid typing of donors to support HNA alloimmunized patients who require HNA-compatible blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 27 publications
8
41
0
3
Order By: Relevance
“…Genotype and allele frequencies of HNA‐3 in the populations of this study were compared with those published for other populations (Table ). The HNA‐3b/3b genotype frequency among the Zhuang population is 8.6%, which is similar to the frequencies reported in the Dong population of our study and to those reported for Chinese Han (He et al., ; Xia et al., ), Japanese (Matsuhashi et al., ), Thai (Changsri et al., ), German and Turkish populations (Hauck et al., ), but significantly higher than previously described in the African American (Huvard, Schmid, Stroncek, & Flegel, ), Brazilian (Lopes et al., ) and English Caucasian populations (Cardoso, Chong, Lucas, Green, & Navarrete, ) ( p < .05). The observed 7% frequency of HNA‐3b/3b in the samples from the Chinese Dong is lower than in the Zhejiang Han (He et al., ), but significantly higher than in African Americans (Huvard et al., ) ( p < .05).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Genotype and allele frequencies of HNA‐3 in the populations of this study were compared with those published for other populations (Table ). The HNA‐3b/3b genotype frequency among the Zhuang population is 8.6%, which is similar to the frequencies reported in the Dong population of our study and to those reported for Chinese Han (He et al., ; Xia et al., ), Japanese (Matsuhashi et al., ), Thai (Changsri et al., ), German and Turkish populations (Hauck et al., ), but significantly higher than previously described in the African American (Huvard, Schmid, Stroncek, & Flegel, ), Brazilian (Lopes et al., ) and English Caucasian populations (Cardoso, Chong, Lucas, Green, & Navarrete, ) ( p < .05). The observed 7% frequency of HNA‐3b/3b in the samples from the Chinese Dong is lower than in the Zhejiang Han (He et al., ), but significantly higher than in African Americans (Huvard et al., ) ( p < .05).…”
Section: Resultssupporting
confidence: 91%
“…() and also English Caucasian populations as revealed by Cardoso et al. (). Therefore, the Chinese Zhuang population may have a higher probability of producing anti‐HNA‐3a antibodies which is clinically associated with TRALI, compared with African American, Brazilian and English Caucasian populations.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, HNA‐3 genotype distribution did not show any significant difference between Hong Kong Chinese and Germans ( P = 0·606), whereas a marginally significant difference between Chinese and British populations ( P = 0·049) was observed (Table ). The allele frequency of HNA‐3a was 71·0% in Hong Kong Chinese population, and it was quite similar to frequencies of 74·4% in German and 76·8% in British populations (Hauck et al, ; Cardoso et al, ). Surprisingly, Bowens et al .…”
Section: Discussionmentioning
confidence: 99%
“…The SLC44A2*2 allele frequencies vary among populations and range in the Han population from 38.2% (Nanning) to 26.2% (Guangzhou) . Although TRALI is much less frequently reported in China than in the United States, the susceptible allele SLC44A2*2 is more prevalent in any East Asian population compared to 17% in Caucasians and 7% in African Americans …”
mentioning
confidence: 99%